Genes KIR, seus ligantes HLA e polimorfismo do gene MICA na toxoplasmose ocular e nas formas clínicas da doença de chagas crônica - Ayo, Christiane Maria (2017)
Ocular toxoplasmosis, characterized by an intraocular inflammation, is the most common clinical manifestation of toxoplasmosis, the infectious disease caused by the protozoan Toxoplasma gondii. The lesions can affect the macula and other layers of the retina and the choroid, resulting in retinochoroiditis with different degrees of ocular involvement. Chagas disease is resulting from infection by the protozoan Trypanosoma cruzi. After 20 years of infection, about 30% develop chronic Chagas heart disease, which is clinically manifested by malignant ventricular arrhythmia, thromboembolism, sudden cardiac death, and chronic heart failure. Ten per cent of Chagas patients present the digestive form of the disease, characterized mainly by dilatations of the esophagus and/or colon, due to the denervation process. The progression of the infection, as well as the development of the different clinical forms and different degrees of severity may be related to genetic characteristics of the pathogen and the host. Among the factors related to the host, the immunological response is of special interest with genetic markers playing an important modulating role in this context as they may contribute to the pathogenesis or resistance in the clinical course of these infections. Objective: The present study aimed to verify the hypothesis that KIR genes, their HLA ligands and MICA gene polymorphisms are associated with ocular toxoplasmosis (OT) and the different clinical forms of Chagas disease. Patients and Methods: This study included 297 patients with toxoplasmosis, 148 clinically diagnosed with OT and 149 without OT. Moreover, 267 patients with Chagas disease were enrolled: 78 clinically diagnosed with the digestive form of the disease, 107 with the cardiac form and 82 with the mixed form. The ELISA technique was used to confirm infection by T. gondii and T. cruzi. Polymorphisms of the KIR and MICA genes were identified by PCR-SSOP and nested PCR. Continuous variables were compared using the unpaired t test and the Chi-square test with Yates correction or the Fisher's exact test were used compare the other results. Results: In relation to the toxoplasmosis, MICA genotypes and alleles did not differ between patients with and without OT, or between patients with the primary or recurrent manifestations of the disease. KIR3DS1 gene was positively associated with the development of OT. KIR activating genes along with their HLA ligands (KIR3DS1+/Bw4-80Ile+, KIR2DS1+/C2+ and KIR3DS1+/Bw4-80Ile+) were associated with susceptibility to OT and both its primary and recurrent clinical manifestations. The inhibitory pairs - KIR2DL3/2DL3-C1/C1 and KIR2DL3/2DL3-C1 - were associated with resistance to OT and its clinical manifestations, whereas the combination KIR3DS1-/KIR3DL1+/Bw4-80Ile+ was a protection factor for the development of OT and, in particular, against recurrent manifestations. As for Chagas disease, The MICA-129met allele was associated with the development of left ventricular systolic dysfunction (LVSD) in patients with chronic chagasic cardiomyopathy, while the MICA-129val allele was associated with a protection of developing LVSD. In particular, the MICA-129 met/met homozygous haplotype was associated with the development of severe LVSD and the MICA-129 val/val homozygous genotype protected against this condition. It was also possible to demonstrate that the haplotype MICA*008~HLA-C*06 and the combination between KIR genes and their HLA ligands - KIR2DS2-/KIR2DL2-/KIR2DL3+/C1+ - were associated with susceptibility for the digestive clinical form of Chagas disease. Conclusions: Our results demonstrate that KIR genes may influence both OT and the clinical digestive form of Chagas disease, whereas the MICA gene may influence the clinical forms of Chagas disease, but not the development of OT.